2017
DOI: 10.1186/s12885-017-3515-y
|View full text |Cite
|
Sign up to set email alerts
|

Levels of activated platelet-derived microvesicles in patients with soft tissue sarcoma correlate with an increased risk of venous thromboembolism

Abstract: BackgroundMicrovesicles are small vesicles expressing specific antigens from their cells of origin. Elevated levels of microvesicles have been shown to be associated with coagulation disorders as well as with different types of malignancies. This study aims to evaluate a possible correlation of different microvesicle subpopulations with a positive history of venous thromboembolism (VTE) in patients with soft tissue sarcoma.MethodsAnnexin V - positive microvesicles, leukocyte (CD45-positive), platelet (CD61-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In contrast, a growing body of literature on PMPs supports their potential contribution to VTE in cancer patients. Previous reports have shown increased plasma levels of PMPs in cancer patients vs. healthy controls, with increased levels correlated with tumor grade (254)(255)(256). Importantly, high plasma PMP levels are correlated with poor overall survival from prostate cancer and higher risk of metastasis in both prostate and gastric cancer, where PMPs can be used as predictors of metastatic disease with high sensitivity and specificity (255,257).…”
Section: Hypercoagulability In Cancer Patientsmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, a growing body of literature on PMPs supports their potential contribution to VTE in cancer patients. Previous reports have shown increased plasma levels of PMPs in cancer patients vs. healthy controls, with increased levels correlated with tumor grade (254)(255)(256). Importantly, high plasma PMP levels are correlated with poor overall survival from prostate cancer and higher risk of metastasis in both prostate and gastric cancer, where PMPs can be used as predictors of metastatic disease with high sensitivity and specificity (255,257).…”
Section: Hypercoagulability In Cancer Patientsmentioning
confidence: 98%
“…Cancer patients with a history of VTE have higher plasma levels of PMPs than cancer patients with no prior VTE events (113,256). These vesicles are derived from both resting and activated platelets and only a minority expressed TF (113,256). Importantly, Bucciarelli et al observed that PMPs could be an independent predictor of overall VTE risk, supporting the use of PMPs as a biomarker to identify patients at high risk of VTE, with or without cancer.…”
Section: Hypercoagulability In Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this, MV-bound TF can be detected in a variety of diseases, including trauma, sepsis, and cancer ( 35 , 36 ). This so-called “blood-borne” TF may contribute to the development of thrombosis that is associated with these diseases ( 36 39 ).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…As particles naturally secreted from the cell, EV has been identified as vital mediators of paracrine communication (Batiz et al, 2015;Jing et al, 2018) and demonstrated a key role in different processes, such as angiogenesis (Qi et al, 2016), antigen presentation (Shenoda and Ajit, 2016), apoptosis (Qi et al, 2019), coagulation (Fricke et al, 2017), cellular homeostasis (Takahashi et al, 2017), inflammation (Zhang S. et al, 2019).…”
Section: Extracellular Vesicles (Ev) Ev: Definition Classification mentioning
confidence: 99%